Pollination of Guarianthe skinneri, an ornamental food deception orchid in southern Florida, by the naturalized orchid bee Euglossa viridissima - W. Pemberton, Robert (Lankesteriana: International Journal on Orchidology, 2007)
A Mesoamerican orchid bee Euglossa viridissima, recently naturalized in Florida, is pollinating cultivated plants of Guarianthe skinneri, also native to Mesoamerica. The flowers were found to be self compatible and nectarless. Of 25 bees observed to visit 31 G. skinneri flowers, 18 picked up pollinaria, and 17 of the bees left the plant after visiting a single flower of this food deception orchid. The bee’s behavior lends support to the idea that food deception pollination systems reduce geitonogamy and promote outcrossing. Cultivated G. skinneri plants growing where the orchid bee occurs in Florida are fruiting which creates the possibility of the naturalization of this orchid. Euglossa viridissima is probably a pollinator of G. skinneri in Mesoamerica where they co-occur.